Review of applications and user perceptions of smart home technology for health and environmental monitoring. Issue 3 (11th May 2022) - Rhee, Jee Heon; Ma, Jae Hoon; Seo, JoonOh; Cha, Seung Hyun
Abstract: In recent decades, smart home technology has advanced, improving the well-being and quality of life of its users. Thus, its applications have expanded, particularly in health and environmental monitoring. Numerous devices have been developed to accommodate user requirements of monitoring; however, the adoption of monitoring devices is closely related to user perception. User perception can be considered from different perspectives. One method of understanding different user perceptions is comparing wearable and nonwearable devices, owing to the differences in their obtrusiveness. The aim of this study was to systematically review the applications and user perceptions of health and environmental monitoring devices, emphasizing on the wearable and nonwearable distinction. We conducted a focused search of articles related to smart home technology and its user perceptions based on its applications. The inclusion criteria were original and peer-reviewed articles centered on health and environmental monitoring devices. We identified and analysed 159 of the 4476 relevant articles and divided the articles into two categories. The first category comprised health and environmental monitoring and their applications by the type of device. The second category comprised user perceptions of monitoring devices. The devices were grouped into wearable and nonwearable devices for our analysis. We identified user perceptions based on usefulness, ease of use, and privacy. Because wearable and nonwearable devices complement their limitations, we recommend their integration for improving user perception. Graphical Abstract: